Handling Stability of Tractor Semitrailer Based on Handling Diagram - Ren Yuan-yuan; Zheng Xue-lian; Li Xian-sheng (Discrete Dynamics in Nature and Society)
Handling instability is a serious threat to driving safety. In order to analyze the handling stability of a tractor semitrailer, a handling diagram can be used. In our research, considering the impact of multiple nonsteering rear axles and nonlinear characteristics of tires on vehicle handling stability, the handling equations are developed for description of stability of tractor semi-trailer. Then we obtain handling diagrams so as to study the influence of driving speed, loaded mass, and fifth wheel lead on vehicle handling stability. The analysis results show that the handling stability of a tractor semi-trailer when the tractor has two nonsteering rear axles is better than that when the tractor has only one nonsteering rear axle. While the stability in the former case is slightly influenced by driving speed and loaded mass, the latter is strongly influenced by both. The fifth wheel lead is found to only slightly influence handling stability for both tractor semi-trailers. Therefore, to ensure the driving safety of tractor semi-trailers when the tractor has only one nonsteering rear axle, much stricter restraints should be imposed on driving speed, and the loaded mass must not exceed the rated load of the trailer.